Acinetobacter indicus sp. nov., isolated from a hexachlorocyclohexane dump site - Jaya Malhotra; Shailly Anand; Swati Jindal; Raman Rajagopal; Rup Lal (2012)
The taxonomic position of a Gram-negative, non-motile, oxidase negative and catalase positive strain, A648(T), isolated from a hexachlorocyclohexane (HCH) dump site located in Lucknow, India, was ascertained by using a polyphasic approach. A comparative analysis of a partial sequence of the rpoB gene and the 16S rRNA gene sequence revealed that strain A648(T) belonged to the genus Acinetobacter. DNA-DNA relatedness values between strain A648(T) and other closely related members (16S rRNA gene sequence similarity greater than 97%), namely Acinetobacter radioresistens DSM 6976(T), A. venetianus ATCC 31012(T), A. baumannii LMG 1041(T), A. parvus LMG 21765(T) A. junii LMG 998(T) and A. soli JCM 15062(T), were found to be less than 8%. The major cellular fatty acids of strain A648(T) were 18:1ω9c (19.6%), summed feature 3 (15.9%), 16:0 (10.6%) and 12:0 (6.4%). The DNA G+C content was 40.4 mol%. The polar lipid profile of strain A648(T) indicated the presence of diphosphatidylglycerol, phosphatidylethanolamine, followed by phosphatidylglycerol and phosphatidylcholine. The predominant polyamine of strain A648(T) was 1,3-diaminopropane and moderate amounts of putrescine, spermidine and spermine were also detected. The respiratory quinone consisted of ubiquinone with nine isoprene units (Q-9). On the basis of DNA-DNA hybridization, phenotypic characteristics and chemotaxonomic and phylogenetic comparisons with other members of the genus Acinetobacter, strain A648(T) is found to be a novel species of the genus Acinetobacter, for which the name Acinetobacter indicus sp. nov. is proposed. The type strain is A648(T) ( = DSM 25388(T) = CCM 7832(T)).